Effect of brain gym stimulation on developmental outcomes among preschool children - Santri Raminda; Satroda Muryanto; Rinaldi Prima Saputra; Ryanda Masri Kurniawan; Dimas Ning Pangesti (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Cognitive function during early childhood plays an important role in children's learning abilities, problem-solving skills, and school readiness. Appropriate stimulation during the preschool period is essential to optimize cognitive development. Brain Gym has been proposed as a simple physical activity intervention that may enhance cognitive function by stimulating brain integration and neuroplasticity. Purpose: To determine the effect of Brain Gym stimulation on cognitive function among preschool children. Method: This quantitative study employed a one-group pretest-posttest design involving 15 preschool children at the Siger Physio Clinic, Bandar Lampung. Cognitive function was assessed using the Ages and Stages Questionnaire-3 (ASQ-3) before and after Brain Gym intervention administered for 15 minutes, three times per week, for four weeks. Data were analyzed using Gamma and Somers' D tests with a significance level of p<0.05. Results: Statistical analysis showed a significant improvement in cognitive function after Brain Gym intervention (p=0.02). Preschool children who participated in Brain Gym demonstrated better cognitive development outcomes following four weeks of intervention. Conclusion: Brain Gym stimulation significantly improved cognitive function among preschool children and may serve as an effective complementary intervention to support early childhood cognitive development.